Comprehensive Analysis of the Glycolysis-Related Gene Prognostic Signature and Immune Infiltration in Endometrial Cancer - Yang, Xiao; Li, Xingchen; Cheng, Yuan; Zhou, Jingyi; Shen, Boqiang; Zhao, Lijun; Wang, Jianliu (Frontiers in Cell and Developmental Biology, 2022)
Glucose metabolic reprogramming and immune imbalance play important roles in the progression of cancers. The purpose of this study is to develop a glycolysis-related prognostic signature for endometrial cancer (EC) and analyze its relationship with immune function. The mRNA expression profiling of the glycolysis-related genes and clinical data of EC patients were downloaded from The Cancer Genome Atlas (TCGA). We identified a glycolysis-related gene prognostic signature for predicting the prognosis of EC by using The Least Absolute Shrinkage and Selection Operator (LASSO) regression, and found the patients in the high-risk group had worse survival prognosis. Multivariate Cox regression analysis showed that the gene signature was an independent prognostic factor for EC. The ROC curve confirmed the accuracy of the prognostic signature (AUC=0.730). Then, we constructed a nomogram to predict the 1-, 3- or 5-year survival rate of EC patients. The association between the gene signature and immune function was analyzed based on “ESTIMATE” and “CIBERSORT” algorithm, which showed the immune and ESTIMATE scores of patients in the high-risk group were lower, while the low immune and ESTIMATE scores were associated with a worse prognosis of patients. The imbalance of immune cells was also found in high-risk group. Further, the protein of CDK1, a gene in the signature was found to be closely related with prognosis of EC and inhibition of CDK1 could inhibit migration and promote apotosis of EC cells. This study reveals a link between glycolysis-related gene signature and immune, also provides personalized therapeutic targets for EC.